The relationship between perceived values, customer satisfaction and brand loyalty in the context of mobile service providers - Chin, Vui Chung (2011)
This dissertation reports the results of the study focused on describing and understanding the determinants of brand loyalty and the mediating effect of customer's satisfaction in using various mobile phone services. The researcher seeks to contribute to the development of a conceptual framework that integrates perceived values which consists of monetary value, convenience value, social value,emotional value, conditional value, epistemic value, functional value, customer satisfaction and also brand loyalty. The study was carried out among the mobile phone users in Kota Kinabalu and Labuan. For the purpose of this research, the researcher used questionnaire as the main research instrument. Quantitative data obtained were analyzed using Statistical Package for Social Research (SPSS) version 17.0. The result of this study found there is a significant relationship between monetary value, convenience value, social value, and functional value on brand loyalty. In contrast the emotional value, conditional value and epistemic value were found no significant relationship with brand loyalty. Customer satisfaction partially mediates the relationship between social value, monetary value and also functional value. Furthermore it was found that customer satisfaction fully mediates the convenience value. It is hoped that this research provides the implication for differentiated marketing strategies in pursuit to strengthen customer's satisfaction and consequently lead to brand loyalty.